Shear strength degradation mechanism dependent on size increase in RC slender beams by using 3D Rigid-Body-Spring-Method. (February 2023) - Fu, Li; Nakamura, Hikaru; Chi, Shunyuan; Yamamoto, Yoshihito; Miura, Taito
Abstract: This study aims to clarify the mechanism of the size effect on the shear behavior for reinforced concrete (RC) slender beams. Three Dimensional Rigid-Body-Spring-Method (3D RBSM), a basic analytical tool applied in this paper, was first demonstrated to be capable of reproducing the shear behavior of large scaled RC slender beams without and with stirrup. Furthermore, the size effect on the shear behavior of three groups of geometrically similar RC slender beams with shear span-depth ratio a / d of 3.51 classified by different levels of stirrup ratio were quantitatively evaluated, and the mechanism of size effect was explained by investigating on beam and arch actions and localized information such as compressive stress in concrete and crack pattern. The analytical results indicated that the RC beams without stirrup showed evident size effect on the shear strength while the arrangement of stirrups along shear span inhibited the size effect to a great extent. More importantly, it was revealed that the size effect on the shear strength of beams without stirrup was dominant by the size dependence of arch action which resulted from the overall decrease in the level of nominal compressive resultant with increasing effective depth. On the other side, for the beams with stirrup, it was clarified that although the size effect on arch action still existed, it was caused by the change in the slope of arm length for arch action, which was induced by the transformation of diagonal crack pattern with increasing effective depth. However, this transformation of diagonal crack pattern contributed to the increase in nominal beam action. As a result, the decrease in nominal arch action was offset by the increase in nominal beam action in terms of combined size effect.